Analysis of gyaku tsuki in Karate: Injury risk and fitness implications - Fatkhur Rozi; Muhammad Zulqarnain Mohd Nasir; Siti Nursyahiirah Hasan (spdfharmony.com, 2025)
Background: Karate, a traditional martial art, involves various techniques that require a deep understanding of biomechanics to optimize performance and minimize injury risks. One such technique, gyaku tsuki (reverse punch), is frequently used in competitive kumite. However, limited biomechanical analysis focuses on this technique. Aims: This study aims to analyze the biomechanics of gyaku tsuki, identifying the key movement phases, potential injury risks, and the necessary physical fitness components. It also explores the implications of biomechanical optimization for performance and injury prevention. Methods: A qualitative approach was employed using video analysis of one elite karate athlete, BK, a specialist in the -55 kg kumite category. Data was collected from the official YouTube page of the athlete on October 29, 2021. The video was analyzed using Kinovea software for biomechanical motion analysis. Triangulation was performed by comparing the video analysis with interviews from the coach and direct observation of the athlete during competition. Results: The study identified critical factors such as proper foot alignment and body rotation that influence punch effectiveness. Incorrect foot positioning and misalignment of the knee during execution were found to increase injury risk. The analysis also highlighted the importance of physical fitness, particularly power, speed, and coordination, for executing an optimal gyaku tsuki. Conclusion: The findings emphasize the need for biomechanically informed training methods to improve performance and reduce injury risks. Training should focus on optimizing body alignment, strength, and flexibility to enhance the effectiveness of gyaku tsuki.